Comparison Between the Central List and The Vienna Convention For The International Sale of Goods Specific Topics - Lamaud, Emmanuel (Department of Commercial Law, 2014)
A comparative study between the Central list and the Vienna Convention would constitute a useful basis for the interpretation of the Convention in those cases where a uniform interpretation cannot be reached. For the purpose of this topic, the study shall be limited to some specific topics of commercial contracts that are important, in particular in regard to the difficulty of interpretation they represent for the CISG. Accordingly, this dissertation is to be divided into five parts. In the first part the TLDB Principle on good faith is compared with CISG counterpart article 7(1). In the second part, the TLDB Principle on fundamental non-performance is compared with article 25 CISG on fundamental breach of contract. In the third part, the TLDB principles dealing with Force majeure and Hardship are compared with article 79 CISG on Exemption. The fourth part is focused on the specific topic of price determination and the comparison between TLDB Principle IV.5 and Arts. 14(1) and 55 CISG. The fifth and final part deals with damages and the comparison between TLDB Principle VI.1 and article 74 CISG.